Enhancement of biocontrol efficacy of Kluyveromyces marxianus induced by N-acetylglucosamine against Penicillium expansum. (15th March 2023) - Wu, Yalan; Gao, Yufang; Zheng, Xiaodong; Yu, Ting; Yan, Fujie
Highlights: GlcNAc enhances biocontrol efficacy of K. marxianus. GlcNAc enhances K. marxianus stress resistance and inhibition of P. expansum. Defense-related enzyme activities in K. marxianus improve by GlcNAc. GlcNAc stimulates a positive response in the oxidative stress system of K. marxianus. GlcNAc up-regulates proliferation-associated genes by transcriptomic analysis. Abstract: This research aimed to investigate the effect of N -acetylglucosamine (GlcNAc) on the biocontrol activity of Kluyveromyces marxianus and involved possible mechanisms. The results indicated that 0.5% GlcNAc significantly improved the antagonistic efficacy of K. marxianus against Penicillium expansum . GlcNAc supplementation led to increases of biocontrol-related enzymes and stress-resistant substances in K. marxianus including chitinase, β-1, 3-glucanase, trehalose and proline, being beneficial for yeasts vigor maintenance under adverse circumstances. The antioxidative-related enzyme activities in K. marxianus, such as superoxide dismutase (SOD), catalase (CAT) and others, were increased by GlcNAc along with more quickly excess reactive oxygen species (ROS) scavenging. GlcNAc resulted in an enhancement of proliferative capacity in K. marxianus according to the transcriptomic analysis. Consequently, GlcNAc contributed to improvements of K. marxianus in the environmental adaptability and stress resistance. Our study demonstrated that both GlcNAc and K. marxianus could be regarded as potential candidates for postharvest technology application.